The normal to the curve $x^2+2 x y-3 y^2=0$, at (1, 1) : |
meets the curve again in the third quadrant meets the curve again the fourth quadrant does not meet the curve again meets the curve again in the second quadrant |
meets the curve again the fourth quadrant |
The equation of the curve is $x^2+2 x y-3 y^2=0$ ......(i) Differentiating with respect to x, we get $2 x+2 y+2 x \frac{d y}{d x}-6 y \frac{d y}{d x}=0 \Rightarrow \frac{d y}{d x}=\frac{x+y}{3 y-x} \Rightarrow\left(\frac{d y}{d x}\right)_{(1,1)}=1$ The equation of the normal at (1, 1) is $y-1=-1(x-1)$ or, $x+y=2$ ......(ii) The x-coordinates of the points of intersection of (i) and (ii) are given by $x^2+2 x(2-x)-3(2-x)^2=0$ $\Rightarrow 4 x^2-16 x+12=0$ $\Rightarrow x^2-4 x+3=0 \Rightarrow(x-3)(x-1)=0 \Rightarrow x=1,3$ Now, $x=1$ and $x+y=2 \Rightarrow y=1$ $x=3$ and $x+y=2 \Rightarrow y=-1$ Hence, the normal to the curve meets it again at $(3,-1)$ which lies in the fourth quadrant. |